Identifikasi Pengetahuan Manajemen Peralatan dan Prosedur Kerja di Bengkel Mobil di Kabupaten Banyuwangi - Rubiono, Gatut; Qiram, Ikhwanul; Putra, Adi Pratama (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
Management has important role in automotive workshop. Small scale workshops usually have a lack ofbusiness knowledge. This activity is aimed to identify tool and working procedure management knowledge in automotiveworkshops in Banyuwangi district. The identification is done by direct survey and interview to 3 workshop owners. Theresult shows that workshops have not applied business management properly. The workshops need practical managementknowledge which easy to apply for the business